Analysis of the influence of corporate governance on the financial performance of Islamic banks in Indonesia 2016 - 2021 - Rarmizi, Rasyid; Yama Nasaruddin, Indo; Hidayah, Nur; sunardi (Pandawan, 2023)
The reason of the cases is to analyze the impacts of ICG (Islamic Corporate Administration) on the monetary execution of Islamic Commercial Banks in Indonesia amid the period of 2017 to 2022 .The population for this study is made up of 15 Islamic Commercial Banks registered with OJK, and a purposive sampling technique is used to choose seven samples. This study employs a descriptive quantitative method by conducting simple regression tests to evaluate the partial impact of ICG regarding the financial results of Islamic banks. The Return on Assets (ROA) proxies the financial performance in this study. Banking in Indonesia is defined by Law No. 10 of 1998 as a business institution that gathers funds in the form of savings from the community and distributes them into financing and other activities that aim to improve the community's welfare. Islamic banks are one of the two types of banking in Indonesia, and they operate based on Shariah principles. The operation of Shariah banking is supported by Law No. 21 of 2008. In recent years, the number of Islamic banks in Indonesia has grown significantly, with a rise in the number of offices, banks, and assets. The research findings demonstrate that ICG very continuous, partially positive results for the Islamic commercial banking sector in Indonesia from 2017 to 2022. Integrating Islamic Corporate Governance principles into Corporate Governance principles shares the same objectives, including transparency and accountability. As a result, Additional exploration is recommended to examine alternative independent variables that could potentially impact the money related execution of Islamic commercial banks. The show investigate underscores the noteworthiness of ICG in expanding the monetary execution of Indonesian Islamic commercial banks.